2003
DOI: 10.4049/jimmunol.170.5.2367
|View full text |Cite
|
Sign up to set email alerts
|

Oligodeoxynucleotides Without CpG Motifs Work as Adjuvant for the Induction of Th2 Differentiation in a Sequence-Independent Manner

Abstract: The outcomes of immune responses are regulated by various parameters including how Ags are handled by APCs. In this study, we describe the intrinsic immunomodulatory characteristics of oligodeoxynucleotides (ODNs) that improve the Ag presentation by APCs. ODNs (20-mer) containing CpG motifs induced strong Th1-skewed responses. In contrast, those without CpG motifs enhanced cytokine production by effector Th cells without particular skewing toward Th1 responses or induced the differentiation of unprimed CD4+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Phosphorothioate-modified ODNs lacking CpG motifs have similarly strong immunoenhancing activities but induced the differentiation of unprimed CD4 ϩ T cells toward Th2 cells (29,30). These opposite effects of CpG-and non-CpG-ODNs on Th1-Th2 polarization may be related to their opposite effects on IL-12 production.…”
Section: Th1-polarizing and Th2-polarizing Factors Have Opposite Effementioning
confidence: 90%
“…Phosphorothioate-modified ODNs lacking CpG motifs have similarly strong immunoenhancing activities but induced the differentiation of unprimed CD4 ϩ T cells toward Th2 cells (29,30). These opposite effects of CpG-and non-CpG-ODNs on Th1-Th2 polarization may be related to their opposite effects on IL-12 production.…”
Section: Th1-polarizing and Th2-polarizing Factors Have Opposite Effementioning
confidence: 90%
“…2). Although T cells do not bind ODN as effectively as APCs (33,34), preliminary studies in our laboratory established that FITC-labeled suppressive ODN do bind CD3 ϩ T cells (data not shown). In this context, Halpern and Pisetsky (35) recently demonstrated that poly(G) ODN inhibit IFN-␥ production by polyclonally activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we use a novel approach for enhanced Ag uptake by B cells, that is, exposure of B cells to CpG-Ag conjugates. Basically, we took advantage of the previously described dual role of CpG-OVA complexes (14,15,20), that is, enhanced endocytosis via a sequence-nonspecific DNA receptor (15,17,32) as well as sequence-specific activation via endocytosed CpG-DNA that meets TLR9 at cytoplasmatic endosome-like organelles (28,29). This approach makes use of CpG-DNA as a vehicle for endocytosis of linked Ag and, upon endocytosis, as activator of Ag-loaded cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, the function of Toll-like receptor 9 (TLR9) is restricted to the activation of immature DCs into professional APCs, while cross-presenting OVA. However, TLR9 is not involved in CpG-DNA-aided cellular uptake (15,17).…”
mentioning
confidence: 99%